Practice makes perfect complete German grammar - Swick, Edward (New York McGraw-Hill Education, 2023)
For beginning to intermediate German language learners, getting a handle on German grammar is the key to communicating correctly and effectively. In Practice Makes Perfect: Complete German Grammar, you'll find everything you need, all in one place―instruction, clear explanations, and extensive exercises―to build your knowledge and communicate more effectively in German.

Based on the successful approach of the Practice Makes Perfect series, Practice Makes Perfect: Complete German Grammar, Premium Third Edition covers all aspects of German grammar you need to know, from present tense regular verbs to adverb and adjective use. Crystal-clear explanations, realistic examples and extensive array of engaging exercises helps you focus your efforts on the practical aspects of communicating in German. With an additional boost from both the practical and high-frequency vocabulary used throughout the book and an answer key that provides great reference and quick feedback, Practice Makes Perfect: Complete German Grammar is the best, most indispensable resource for upgrading your command of the German language.

• Proven approach to learning helps you get a handle on German grammar right away, and build on your learnings as you go
• Every grammatical point is illustrated with example sentences to illustrate and clarify
• A full chapter of exercises reviews the contents of the entire book
• NEW: Enhanced with new audio recordings, via app, of example sentences and answers to numerous exercises.-- Provided by the publisher
Pronunciation and gender -- Definite and indefinite articles -- Pronouns, plurals, and the verb sein -- Titles, locations, and interrogatives -- The verbs haben and werden and negation -- The present tense and numbers -- Direct objects and the accusative case -- Irregular verbs in the present tense -- Separable and inseparable prefixes and imperatives -- Accusative case prepositions and interrogatives -- Regular verbs in the past tense and word order -- Indirect objects and the dative case -- Irregular verbs in the past tense -- Modal auxiliaries in the present and past tenses -- The accusative-dative prepositions -- Regular verbs in the present perfect tense and more imperatives -- Genitive case, the comparative, and the superlative -- Irregular verbs in the present perfect tense and adjectives -- Past perfect, future, and future perfect tenses -- Relative pronouns -- Modifiers, adverbs, reflexive pronouns, and conjunctions -- Double infinitive structures -- Infinitive clauses -- The passive voice -- The subjunctive -- Final review -- Appendix A: The principal parts of irregular verbs -- Appendix B: Prepositions and their required cases -- Appendix C: Summary of declensions.
Keywords: German language -- Self-instruction.; German language -- Textbooks for foreign speakers -- English; German language. -- Problems, exercises, etc